2013
DOI: 10.1016/j.ajog.2013.05.038
|View full text |Cite
|
Sign up to set email alerts
|

Transplacental transfer and distribution of pravastatin

Abstract: Objectives Determine the bidirectional transfer of pravastatin across the dually perfused term human placental lobule and its distribution between the tissue, maternal and fetal circuits. Study design The transfer of pravastatin was determined in the Maternal-to-Fetal (n=11) and Fetal-to-Maternal (n=10) directions. Pravastatin was co-perfused with its [3H]-isotope and the marker compound antipyrine (20 μg/mL) and its [14C]-isotope. The concentration of pravastatin in the perfused tissue, the maternal and fet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
52
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(60 citation statements)
references
References 21 publications
(20 reference statements)
4
52
0
1
Order By: Relevance
“…Indeed, in human first trimester placental explants, pravastatin inhibits insulin-like growth factor 1 receptor function with adverse implications for trophoblast differentiation (39). With regard to the fetus, the levels of pravastatin achieved within the fetal circulation in this current study are unknown, but earlier studies have demonstrated that transfer of pravastatin in ex vivo human placenta occurs albeit to a limited extent (40,41). However, it is of interest to note that we observed no induction of Vegfa expression in Hsd11b2 −/− fetal heart, suggesting that if pravastatin is eliciting direct effects on the fetus, it may be via different pathways.…”
Section: Discussionmentioning
confidence: 51%
“…Indeed, in human first trimester placental explants, pravastatin inhibits insulin-like growth factor 1 receptor function with adverse implications for trophoblast differentiation (39). With regard to the fetus, the levels of pravastatin achieved within the fetal circulation in this current study are unknown, but earlier studies have demonstrated that transfer of pravastatin in ex vivo human placenta occurs albeit to a limited extent (40,41). However, it is of interest to note that we observed no induction of Vegfa expression in Hsd11b2 −/− fetal heart, suggesting that if pravastatin is eliciting direct effects on the fetus, it may be via different pathways.…”
Section: Discussionmentioning
confidence: 51%
“…Unlike simvastatin, which is hydrophobic, pravastatin is hydrophilic, meaning it may less readily cross through the placenta to the fetus. 11,13 Cohort studies have shown that administration of lipophilic statins have increased fetal malformation risk; however, hydrophilic statins, including pravastatin, have not been associated with an increased risk. 11 A multicenter randomized controlled trial has been undertaken to examine the effect of oral pravastatin on serum sFlt-1 levels in women with preterm preeclampsia, 14 and a separate prevention trial has also started.…”
mentioning
confidence: 99%
“…Moreover, it is not dependent on CYP3A metabolism; therefore, there are no clinically relevant pharmacokinetic interactions between pravastatin and CYP3A inhibitors. Additionally, pravastatin is a substrate of placental efflux transporters such as P-glycoprotein and multidrug resistance-associated protein 2 (17,18). Consistent with these characteristics, recent transplacental studies have shown that the drug's ability to cross the placenta was limited and clearance was higher in the fetal-to-maternal direction than the maternal-to-fetal direction (18).…”
Section: Statins For Treatment Of Preeclampsia And/or Iugr In Women Wmentioning
confidence: 59%
“…Additionally, pravastatin is a substrate of placental efflux transporters such as P-glycoprotein and multidrug resistance-associated protein 2 (17,18). Consistent with these characteristics, recent transplacental studies have shown that the drug's ability to cross the placenta was limited and clearance was higher in the fetal-to-maternal direction than the maternal-to-fetal direction (18). The US randomized controlled trial additionally showed that renal clearance of pravastatin is higher in pregnancy compared with in the nonpregnant state, adding uncertainty to the ideal dose with the safest profile to be used in high-risk pregnant women (15).…”
Section: Statins For Treatment Of Preeclampsia And/or Iugr In Women Wmentioning
confidence: 99%